A Robust Solid Electrolyte Interphase Layer Augments the Ion Storage Capacity of Bimetallic‐Sulfide‐Containing Potassium‐Ion Batteries. (9th September 2019) - Xie, Junpeng; Li, Xiaodan; Lai, Haojie; Zhao, Zhijuan; Li, Jinliang; Zhang, Wanggang; Xie, Weiguang; Liu, Yiming; Mai, Wenjie
Abstract: Metal–organic framework‐derived NiCo2.5 S4 microrods wrapped in reduced graphene oxide (NCS@RGO) were synthesized for potassium‐ion storage. Upon coordination with organic potassium salts, NCS@RGO exhibits an ultrahigh initial reversible specific capacity (602 mAh g −1 at 50 mA g −1 ) and ultralong cycle life (a reversible specific capacity of 495 mAh g −1 at 200 mA g −1 after 1 900 cycles over 314 days). Furthermore, the battery demonstrates a high initial Coulombic efficiency of 78 %, outperforming most sulfides reported previously. Advanced ex situ characterization techniques, including atomic force microscopy, were used for evaluation and the results indicate that the organic potassium salt‐containing electrolyte helps to form thin and robust solid electrolyte interphase layers, which reduce the formation of byproducts during the potassiation–depotassiation process and enhance the mechanical stability of electrodes. The excellent conductivity of the RGO in the composites, and the robust interface between the electrodes and electrolytes, imbue the electrode with useful properties; including, ultrafast potassium‐ion storage with a reversible specific capacity of 402 mAh g −1 even at 2 A g −1 . Abstract : Die Speicherung von Kalium‐Ionen in NiCo2.5 S4 ‐Kompositelektroden verbessert sich unter Verwendung von Kalium‐bis(fluorsulfonyl)imid in einem Ethylen‐/Propylencarbonatgemisch als Elektrolyt. In den Elektrolyten mit KPF6 oder zusätzlichem Fluorethylencarbonat verschlechtert sich die Leistung. Eine stabile Zwischenschicht an der Elektroden/Elektrolyt‐Grenzfläche trägt zur Erhöhung der Leistung in Kalium‐Ionen‐Batterien bei. Skala: 10 μm.